Dominasi Kelompok Elite dalam Pengembangan Pariwisata di Desa Tenganan Pegringsingan - Aprigiyana, I Komang; Noak, Piers Andreas; Ali Azhar, Muhammad (Jurnal Nawala Politika, 2020)
ABSTRACT x This study aims to find out how are the domination of indigenous elites in the tourism development in Tenganan Pegringsingan village. As the theoritical basis, this research uses the theory of Elite by Vilfredo Pareto as a frame of the problems in this study.The results of this study are: first, the Governing Elite is the most dominating group in the tourism development in Tenganan Village. The domination of the indigenous elite can be discovered in policies making related to tourism development without involving non-elite communities who only become the object of the policy. Second, the domination of the indigenous elite is interpreted as the result of traditional power in the indigenous elite of the Tenganan Village, which is able to bind its people in traditional way. Keywords: Elite, Tenganan Pengringsingan Village, Tourism, Power